3−x | ||
f(x)= | ,P=(x0,12) | |
2x+18 |
−1*(2x+18)−2(3−x) | ||
f'(x) = | ||
(2x+18)2 |
−2x−18−6+2x | −24 | −6 | ||||
f'(x) = | = | = | ||||
(2x+18)2 | 4(x+9)2 | (x+9)2 |
1 | ||
f'(x) = | ||
2 |
−6 | 1 | ||
= | |||
(x+9)2 | 2 |
3−x | 1 | |||
= | ⇒ xo= −3 P(−3,1/2) | |||
2x+18 | 2 |
−6 | ||
f'(x)= | ||
(x+9)2 |
−6 | 1 | |||
a=f'(−3) = | = − | |||
36 | 6 |
1 | 1 | |||
y= − | (x+3)+ | |||
6 | 2 |
3−x | 1 | ||
= | |||
2x+18 | 2 |
−6 | −1 | |||
f'(−3) = | = | |||
62 | 6 |
1 | ||
y = − | x + b | |
6 |
1 | ||
U{1}[2} = − | *3+b | |
6 |
1 | 1 | ||
= − | +b | ||
2 | 2 |
1 | ||
y = − | x+1 | |
6 |
1 | 1 | ||
= − | *(−3)+b | ||
2 | 6 |
1 | |
=U{1}[2}+b | |
2 |
1 | ||
y= − | x | |
6 |